Internalization of Citizenship Values ​​through Inquiry Learning Model: Qualitative Study on High School Students - Gunadi, Lie, Epifani R.; Supriadi, Supriadi; Nasir, Mohammad; Dhayinta, Shellya Tanaya (International Journal of Sustainable English Language, Education, and Science, 2025)
This study aims to explore the effectiveness of the inquiry learning model in internalizing citizenship values in senior high school (SMA) students. The approach used is qualitative, with a literature study method that utilizes reputable scientific sources, including national and international journals. The results of the study indicate that the application of the inquiry learning model can increase students' active involvement in the learning process, strengthen critical thinking skills, and encourage a more contextual understanding of citizenship values such as responsibility, tolerance, participation, and social justice. Inquiry learning creates space for students to build understanding through exploratory, collaborative, and reflective processes, thus having an impact on the formation of strong citizenship character and attitudes. In addition, this study identified that the process of internalizing values is not only determined by learning strategies but is also influenced by external factors such as the social environment, culture, education, and media. Thus, inquiry learning is considered relevant to be integrated more widely into education policies in order to strengthen citizenship awareness and form a young generation that is active and responsible in community and national life.